COGNITIVE ASPECT OF TOPONYMIC PHRASEOLOGICAL UNITS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article explores the cognitive aspects of toponymic phraseological units, focusing on how geographical names embedded in idiomatic expressions reflect and structure human conceptualization of space, culture, and social experience. Drawing on the principles of cognitive linguistics and cultural linguistics, the study examines how such units function as mental representations that encode collective knowledge, cultural associations, and evaluative attitudes toward specific places and the people associated with them. The research highlights that toponymic phraseological units are not arbitrary linguistic formations but are grounded in conceptual metaphors, image schemas, and culturally shared cognitive models. The analysis demonstrates that these expressions play a significant role in shaping worldview by linking physical geography with abstract social meanings.
Keywords: Toponymic phraseological units, cognitive linguistics, conceptual metaphor, cultural linguistics, idioms, mental representation, worldview, image schema, stereotype formation, linguistic cognition.